2010
DOI: 10.1159/000322001
|View full text |Cite
|
Sign up to set email alerts
|

In Search of the Optimal Oxygen Saturation for Extremely Low Birth Weight Infants: A Systematic Review and Meta-Analysis

Abstract: Background: The optimal arterial oxygen saturation in the first weeks of life is unknown for immature newborn infants. Objectives: To determine the effect of targeting high versus low oxygen saturation in the first weeks of life on the outcome of very low and extremely low birth weight infants. Methods: Randomized and observational studies were sought that compared the outcomes in babies with high or low oxygen saturation targeting assessed by pulse oximetry. Results: Ten studies were identified, of which 8 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 71 publications
0
63
0
3
Order By: Relevance
“…Higher SpO 2 targets may induce stable sleep patterns and better long-term growth and development (32), but at the cost of retinopathy of prematurity, bronchopulmonary dysplasia, and brain injury (33,34). Alternately, the use of "restrictive" oxygen therapy has been found to produce a negative effect on the survival, cognitive functions, adaptive skills and behavior (35).…”
Section: Discussionmentioning
confidence: 99%
“…Higher SpO 2 targets may induce stable sleep patterns and better long-term growth and development (32), but at the cost of retinopathy of prematurity, bronchopulmonary dysplasia, and brain injury (33,34). Alternately, the use of "restrictive" oxygen therapy has been found to produce a negative effect on the survival, cognitive functions, adaptive skills and behavior (35).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a randomized study confirmed that a low oxygen saturation (85–89%) compared with a high (91–95%) reduces ROP [95]. In a recent systematic review, we showed that a low SpO 2 reduces severe ROP by more than 50% and BPD by 20–25% [96]. Unfortunately, it seems that mortality is also significantly increased if babies <29 weeks’ gestation are kept in SpO 2 between 85 and 89% compared with 91–95% [95,97].…”
Section: Oxygenation Of Term and Preterm Newborn Infantsmentioning
confidence: 94%
“…In the following years, several cohort studies all strongly indicated that a lower SpO 2 target is preferable compared with a high target [15,16,17,18,19,20,21]. We summarized these studies and found a more than 50% significant reduction in severe ROP and a 20-25% reduction in bronchopulmonary dysplasia (BPD)/chronic lung disease when the SpO 2 target was low compared to high [22]. No difference in mortality was detected by any of these studies including two systematic reviews and meta-analysis [22,23].…”
Section: Introductionmentioning
confidence: 99%